Research competence among academics at a private higher education institution in South Africa - Eugene Lee Davids (University Babes-Bolyai, 2022)
The divide between private and public higher education in South Africa has shed light on the unknown contributions of private higher education institutions to national research production. Many private higher education institutions are changing toward becoming research-intensive to meet the demands and contributions toward knowledge generation and dissemination. The shift toward becoming research-intensive means the role of academic staff is rapidly evolving. The current study aimed to determine how academic staff at a private higher education institution in South Africa identified their competence as researchers, particularly due to the changing landscape from a teaching and learning-intensive to a research-intensive institution. Using a survey design, the study included 124 academic staff at a private higher education institution. The results suggest that most academic staff identified their research competence as being emerging researchers (71.77%). Furthermore, when examining the factors academic staff provide as reasons for their research competence, being motivated by students and classroom-based activities, yearning to belong and being part of a research culture as well as research competency booster emerged as relevant factors. The results provide an initial opportunity for reflection and outlines recommendations for practice that could assist private and public higher education institutions in the change toward a research-intensive institution.